Head and neck cancer survivorship consensus statement from the American Head and Neck Society. Issue 1 (30th November 2021) - Goyal, Neerav; Day, Andrew; Epstein, Joel; Goodman, Joseph; Graboyes, Evan; Jalisi, Scharukh; Kiess, Ana P.; Ku, Jamie A.; Miller, Matthew C.; Panwar, Aru; Patel, Vijay A.; Sacco, Assuntina; et al.
Abstract: Objectives: To provide a consensus statement describing best practices and evidence regarding head and neck cancer survivorship. Methods: Key topics regarding head and neck cancer survivorship were identified by the multidisciplinary membership of the American Head and Neck Society Survivorship, Supportive Care & Rehabilitation Service. Guidelines were generated by combining expert opinion and a review of the literature and categorized by level of evidence. Results: Several areas regarding survivorship including dysphonia, dysphagia, fatigue, chronic pain, intimacy, the ability to return to work, financial toxicity, lymphedema, psycho‐oncology, physical activity, and substance abuse were identified and discussed. Additionally, the group identified and described the role of key clinicians in survivorship including surgical, medical and radiation oncologists; dentists; primary care physicians; psychotherapists; as well as physical, occupational, speech, and respiratory therapists. Conclusion: Head and neck cancer survivorship is complex and requires a multidisciplinary approach centered around patients and their caregivers. As survival related to head and neck cancer treatment improves, addressing post‐treatment concerns appropriately is critically important to our patient's quality of life. There continues to be a need to define effective and efficient programs that can coordinate this multidisciplinary effort toward survivorship.